Colourless p-phenylene-spaced bis-azoles for luminescent concentrators. (November 2016) - Bellina, Fabio; Manzini, Chiara; Marianetti, Giulia; Pezzetta, Cristofer; Fanizza, Elisabetta; Lessi, Marco; Minei, Pierpaolo; Barone, Vincenzo; Pucci, Andrea
Abstract: We report on the synthesis of new push-pull imidazole-benzothiazole and thiazole-benzothiazole fluorophores obtained in good yields by using direct CH arylation synthetic strategies. Spectroscopic investigations in CHCl3 solution evidenced that the 1, 4-phenylene-spaced imidazole-benzothiazole bearing an electron-donating dimethylamino group achieved a trade-off between fluorescence maximum (516 nm), Stokes shift (165 nm) and a quantum yield higher than 0.4. Dispersions of the selected fluorophore in poly (methyl methacrylate) (PMMA) thin films mostly maintained the optical features in solution with significant light transmittance in the visible region (90% at 440 nm), and a brilliant green emission at 500 nm. Photocurrent experiments performed on PMMA thin films coated over high purity transparent glasses promoted their use in the development of colourless luminescent solar concentrators with optical efficiencies close to 6%. Graphical abstract: Highlights: New near-UV absorbing fluorophores with bis-azoles backbones were synthesized. Dimethylamino imidazole-benzothiazole showed SS > 150 nm and Φf > 0.4 in CHCl3 . PMMA thin films displayed brilliant green emission and SS > 130 nm. The high VIS transmittance and ηopt near 6 support the realization of colourless LSC.